A cross sectional descriptive study of hand washing knowledge and practices among primary school children in Mumbai, Maharashtra, India - Gawai, Priyanka P.; Taware, Sachin A.; Chatterjee, Ameeta S.; Thakur, Harshad P. (International Journal Of Community Medicine And Public Health, 2016)
Background: Hand washing has been widely accepted worldwide as a cost effective intervention to prevent the spread of communicable diseases. However, despite proven effectiveness, practices of hand washing have found to be poor in developing nations. As children are vulnerable to communicable diseases, the present study aims to assess hand washing knowledge and practices among primary school children in municipal schools in Mumbai. Methods: A cross sectional descriptive study was carried out among randomly selected primary school children of municipal corporation schools in Mumbai, India. Two thousand two hundred and eighty three students were interviewed using a structured interview schedule regarding socio-demographic characteristics, history of illness and hand washing knowledge and practices. Results: More than half (54%)of the study population reported a history of illnesses in the past one month, out of which 81.4% reported absenteeism due to illness. Around 34% children were unaware about health related consequences of not washing hands. When asked about the important times when hands ought to be washed, only 18% mentioned after toilet use. Of the 2283 students, a very small percentage of respondents (0.7%) reportedly practiced five steps of hand washing; only 1% practiced four steps of hand washing. Forgetfulness was cited as the primary reason for missing washing hands before eating food (88%) and after toilet use (84%). Conclusions: Knowledge regarding hand washing was found to be inadequate while practices were not up to the recommended standard. This suggests that both behaviour change education and infrastructure improvements are equally important to improve hand washing practices in the long run.